Las Cirugías Estéticas como Manifestación De La Histeria en La Posmodernidad. Relato De Cuatro Mujeres Respecto a la Modificación Corporal - Ríos, Yeni Marcela (Universidad Antonio Nariño, 2024)
The body is recognized by the subject through three dimensions: a real, where is the body of sensations, desires and enjoyment, an imaginary, which is the body that looks like a globally formed silhouette, perceiving always out the subject, as in a mirror, in an image or the other, and a token, which will be composed of signifiers that became important, arranged both by the person, and by society